2022
DOI: 10.1126/sciadv.abm1831
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal single-cell RNA-seq analysis reveals stress-promoted chemoresistance in metastatic ovarian cancer

Abstract: Chemotherapy resistance is a critical contributor to cancer mortality and thus an urgent unmet challenge in oncology. To characterize chemotherapy resistance processes in high-grade serous ovarian cancer, we prospectively collected tissue samples before and after chemotherapy and analyzed their transcriptomic profiles at a single-cell resolution. After removing patient-specific signals by a novel analysis approach, PRIMUS, we found a consistent increase in stress-associated cell state during chemotherapy, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
146
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(150 citation statements)
references
References 86 publications
4
146
0
Order By: Relevance
“…However, we found 7 out of the 11 non-concordant markers to be immediate-early genes (IEGs). IEG expression has been described to be rapidly induced by a number of stimuli, including protease treatment, tissue dissociation or inflammatory signals from the tumor microenvironment 31, 32, 33 . Of note, EOC382_pOme tumor sample preparation was extraordinarily harsh and involved multiple additional filtering and gradient purification steps, which could have induced additional cell stress.…”
Section: Resultsmentioning
confidence: 99%
“…However, we found 7 out of the 11 non-concordant markers to be immediate-early genes (IEGs). IEG expression has been described to be rapidly induced by a number of stimuli, including protease treatment, tissue dissociation or inflammatory signals from the tumor microenvironment 31, 32, 33 . Of note, EOC382_pOme tumor sample preparation was extraordinarily harsh and involved multiple additional filtering and gradient purification steps, which could have induced additional cell stress.…”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al identified several gene signatures among treatment-naïve HGSOC populations such as proliferative DNA repair, RNA processing, TCA cycle, among others. Strikingly, however, HGSOC populations post-neoadjuvant chemotherapy were enriched for a stress-associated profile (see Table 2) [56]. Pools of HGSOC cells with a similar stress profile have also been identified as likely sources of relapse-initiating cells [57].…”
Section: Discussionmentioning
confidence: 99%
“…Several modes of resistance have been identified in in vitro studies to either paclitaxel or platinum-based drugs, and studies using clinical samples have been critical in identifying the common traits of cancer cells; however, treatment efficacy and future drug development would greatly benefit from the ability to differentiate between resistant populations that are primed by the TME and those that are not. Critically, by characterizing 22 matched pre-and post-neoadjuvant chemotherapy-treated HGSOC patient samples, Zhang et al demonstrated that treatment enriches subpopulations with an initially increased transcriptomic stress response and primes HGSOC cells to resist chemotherapy [56]. Kan et al similarly identified that relapseinitiating HGSOC cells can largely originate from a subpopulation early in tumorigenesis with a high-stress signature.…”
Section: Chemorefractory Hgsoc Highlights the Priming Capabilities Of...mentioning
confidence: 99%
See 1 more Smart Citation
“…CNV profiles for the individual cancer cells for each sample were obtained with InferCNV (1.7.1) 49 using a common set of stromal cells from a previously published data 50 as references. The Leiden algorithm was used for determining the underlying subclonal populations based on the CNV profiles.…”
Section: Methodsmentioning
confidence: 99%